Cladonia confusa fm. confusa f. confusa - Yánez-Ayabaca, A.; Ahti, T.; Bungartz, F. (Zenodo, 2013)
Cladonia confusa f. confusa (Figs. 3a, c–d) Podetia yellowish to green gray, with pale brown tips. Spot tests and chemistry : P−, K−, C−, KC+ yellow, UV+ bright greenish white; perlatolic and usnic acids (perlatolic acid rarely absent and then UV–, see notes below). Distribution and ecology : Known from Fernandina, Isabela, Pinta, Pinzón, San Cristóbal, Santa Cruz, and Santiago Island. The most common Galapagos reindeer lichen. Often the dominant taxon in lichen heaths of the humid highlands, where it can form gigantic cusions up to several meters in diameter. Few specimens have also been collected in humid habitats at lower altitudes, in the transition or even dry zone. Notes : The large mayority of specimens of C. confusa f. confusa contains perlatolic acid and thus fluoresces a bright greenish white under UV light. This is not the case, however, for some specimens that also morphologically differ from typical C. confusa f. confusa . These specimens that lack perlatolic acid contain an unidentified substance that forms a pale spot at R f 1−2 in solvent A. Morphologically the latter two chemotypes are very similar and extremely difficult to distinguish. The atypical chemotype generally appears to have ± finer, but relatively compact podetia, almost exclusively dichotomously ramified, with a rather “bumpy” surface, covered with broad, relatively flat, closely adjoining packets of algae, giving the podetia a overall rather roughened surface aspect (see inset of Fig. 3d). In contrast, typical Cladonia confusa f. confusa (Fig. 3c) is characterized by mostly trichotomous ramifications, although specimens frequently also have dichotomously ramified podetia. In fact the majority of the terminal branches are dichotomous, only further down ramifications become increasinly trichotomous. Overall these typical specimens also have a more slender, less stout, less densely ramified appearance, though individual podecia are generally slightly thicker, i.e., generally somewhat broader in diameter. The different surface seems to ...